2016
DOI: 10.18001/trs.2.4.11
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Point of Sale Tobacco Marketing Using Behavioral Laboratory Methods

Abstract: With passage of the 2009 Family Smoking Prevention and Tobacco Control Act, the FDA has authority to regulate tobacco advertising. As bans on traditional advertising venues and promotion of tobacco products have grown, a greater emphasis has been placed on brand exposure and price promotion in displays of products at the point-of-sale (POS). POS marketing seeks to influence attitudes and behavior towards tobacco products using a variety of explicit and implicit messaging approaches. Behavioral laboratory metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 125 publications
0
4
0
Order By: Relevance
“…In addition, a systematic review by Paynter et al ,52 which included 12 peer review studies, concluded that exposure to tobacco advertisements at PoS increased the likelihood of SS, as such exposure increased the perceived attractiveness of smoking and brand awareness. PoS tobacco marketing is designed to increase memorability through the mechanism of the mere exposure effect based on the limited amount of cognitive resources for perceiving, comprehending and remembering the information that the individual encounters in their environment 53. Both the direct (exposed cigarettes) and indirect (brand image) visual smoking cues, as well as related content such as tagline, commercial message and health warnings, help boost the memory of the tobacco products in the exposed population.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a systematic review by Paynter et al ,52 which included 12 peer review studies, concluded that exposure to tobacco advertisements at PoS increased the likelihood of SS, as such exposure increased the perceived attractiveness of smoking and brand awareness. PoS tobacco marketing is designed to increase memorability through the mechanism of the mere exposure effect based on the limited amount of cognitive resources for perceiving, comprehending and remembering the information that the individual encounters in their environment 53. Both the direct (exposed cigarettes) and indirect (brand image) visual smoking cues, as well as related content such as tagline, commercial message and health warnings, help boost the memory of the tobacco products in the exposed population.…”
Section: Discussionmentioning
confidence: 99%
“…95 96 Eye tracking and functional magnetic resonance imaging (fMRI) would also improve researchers' understanding of how tobacco displays and other retail marketing stimulate craving and deter cessation. 97 For example, research that combined GPS tracking (to identify which tobacco retailers participants encountered) and fMRI (showing participants tobacco storefronts they visited and did not visit) observed differential neurobiological responses to more frequently visited tobacco storefronts. 98 Integrating novel methods may provide better insight on causal and modifiable mechanisms that perpetuate tobacco use, including tobacco displays, price discounts, as well as branded and unbranded tobacco cues in the retail environment.…”
Section: Future Directionsmentioning
confidence: 99%
“…EMA and GEMA have also been used to document real-time exposure to retail tobacco marketing as well as inequities in exposure 95 96. Eye tracking and functional magnetic resonance imaging (fMRI) would also improve researchers’ understanding of how tobacco displays and other retail marketing stimulate craving and deter cessation 97. For example, research that combined GPS tracking (to identify which tobacco retailers participants encountered) and fMRI (showing participants tobacco storefronts they visited and did not visit) observed differential neurobiological responses to more frequently visited tobacco storefronts 98.…”
Section: Reducing Visibility: Tobacco Point-of-sale Display Bansmentioning
confidence: 99%
“…This special issue also contains a review from Robinson et al 78 of human behavioral laboratory methods that can be adapted to evaluate the impact of point of sale tobacco marketing on the attention, memory, implicit attitudes and behavior of smokers, while Tidey et al 79 contribute a review of how behavioral economic laboratory measures provide an expedited simulation of the behavioral effects of tobacco control policies within specific subpopulations of interest to FDA. These laboratory approaches are particularly important to tobacco regulatory science because the behavior of persons under the age of 18 is especially sensitive to the influence of tobacco product advertising and to product cost.…”
mentioning
confidence: 99%